Application of the FM to Models with Confining Potentials - Arteca, Gustavo Alberto (1990)
Quantum mechanical models with confining potentials have deserved remarkable attention in recent years, because they provide convenient phenomenological potentials to explain the hadronic spectroscopy within the context of quark theory. The aim of this chapter is to employ the FM to calculate the eigenvalues of these models by purely numerical approaches and also to derive accurate analytical expressions. We do not discuss here the applicability of the model, since this question is beyond the scope of this book. However, the interested reader may resort to Appendix F for additional details about the importance and usefulness of the confining models in elementary particle physics.